Bydgoszcz w okresie I wojny światowej (Kronika Bydgoska, 2014)
In the early 20th century, Bydgoszcz was undoubtedly the most Germanized city in the Poznań Province. German population accounted for about 80%. It was situated only 50 km away from the Prussian-Russian border. During World War I, it became a front city, lying about 100 km away from the Eastern Front outlined in 1915. Despite the fact that Bydgoszcz was not affected by direct warfare, the city had fully felt its effects, including problems with food supplies, lack of labor force, and increasing community dissatisfaction. The attitude of the Poles living in Bydgoszcz in relations to the Germans had undergone a significant evolution, from loyalist position, waiting to undertaking national-liberation activities. Affiliation of the city, just like the vast part of the region of Wielkopolska, to the Polish State was not obvious during signing of the Armistice of Compiegne on November 11, 1918. Only signing of the Treaty of Versailles of June 28, 1919 by the German delegation had finally ended any discussions and disputes regarding this topic.